RECONSTRUCTION OF STANDARD CLAUSES IN ELECTRONIC CONTRACTS IN INDONESIA: THE VALUE ORIENTATION OF DIGNIFIED JUSTICE - Karo, Rizky Karo; Stefana, Violent Ester; Kumagap, Elsa Finelia; Sugianto, Joanne Natasha (Faculty of Law, Universitas Tanjungpura, 2024)
AbstractThe rapid and advanced achievement of internet technology makes it easier to access any information needed, including product information. The existence of this facility makes it a very important potential to influence trade patterns, especially electronic transactions through e-commerce which are legally bound to electronic contracts. Electronic contracts have standard clauses, Standard clauses have the benefit of saving the parties' usage and transaction time. Electronic contracts containing standard clauses have the potential to violate the law and damage the dignity of users if they do not comply with the Law on Electronic Information and Transactions. The research method used is the normative juridical research method. Researchers use secondary data in the form of primary, secondary, and tertiary legal materials and use qualitative analysis. The results of the study, namely the value of Dignified Justice, aim to humanize people, in this case, to provide justice for consumers and business actors in electronic contracts. AbstrakKemajuan teknologi dan informasi melalui jejaring internet memberikan kemudahan dalam mengakses informasi dan kebutuhan manusia secara pesat dan cepat. Adanya kemudahan tersebut membuatnya menjadi suatu potensi yang sangat penting untuk dapat mempengaruhi pola perdagangan, terkhusus transaksi elektronik melalui e-commerce yang secara yuridis terikat kepada kontrak elektronik. Kontrak elektronik memiliki klausula baku, klausula baku memiliki manfaat untuk menghemat waktu penggunaan dan transaksi para pihak. Kontrak elektronik yang bermuatan klausula baku berpotensi melanggar hukum dan merusak martabat pengguna apabila tidak mematuhi Undang-Undang tentang Informasi dan Transaksi Elektronik. Metode penelitian yang digunakan yakni metode penelitian yuridis normatif. Peneliti menggunakan data sekunder berupa bahan hukum primer, bahan hukum sekunder, dan tersier, serta menggunakan analisis kualitatif. Hasil penelitian yakni nilai keadilan bermartabat bertujuan untuk memanusiakan manusia, dalam hal ini untuk memberikan keadilan bagi konsumen dan pelaku usaha dalam kontrak elektronik.